Women And Men In Rural Microfinance: The Case Of Uganda - Hans Dieter Seibel; Gloria Almeyda (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2002)
Uganda, where 85 % of the population live in rural areas, has experienced a rapid rise of rural and microfinance over the last ten years. There is a pronounced gender awareness in public policities and programs. Best practices have been mastered by institutions in the formal and the NGO sector. In the latter, women dominate as borrowers. Yet, as the vast majority still have no access to deposit and credit services, expansion of outreach remains as the biggest challenge. Rapid expansion of sustainable financial services to women is best achieved in Uganda not through women-only programs, but by a broad range of financial institutions with unbiased services to both women and men, the poor and the near-poor. NGO-supported microfinance institutions (MFIs), through group lending up to a ceiling, have provided start-up finance, particularly for women; but this has added borrower transaction costs and restricted growth. In Centenary Rural Development Bank and some MFIs, voluntary savings and individual lending to enterprising men and women have fostered sustainable farm and nonfarm business growth beyond the poverty line, creating at the same time employment opportunities for the very poor. Under the prevailing conditions of a conducive policy environment, diversified agricultural and microenterprise opportunities, good practices in agriculture and microfinance, and effective agency coordination, the most effective means of donor assistance are equity investments in rural banks to extend their branch network and staff; equity investments in MFIs to transform into regulated deposit-taking institutions; support to banks and MFIs for staff selection and training; the facilitation of linkages between MFIs and banks; and the development of gender-sensitive strategies in different culture areas of Uganda based on the differential analysis of customer information in each institution?s management information system.
Keywords: 330; Mikrofinanzierung; Ländlicher Finanzmarkt; Agrarkredit; Geschlecht; Frauenpolitik; Uganda